SOSIALISASI BUDIDAYA TANAMAN OBAT KELUARGA KEPADA MASYARAKAT LINGKUNGAN RW04 KEL.SEPANJANGJAYA, KEC.RAWALUMBU, KOTA BEKASI - Muhammad Sugiarto; Asep Saiful Bahri; Hermanto Hermanto (An-Nizam, 2022)
Family medicinal plants are plants that have many benefits, especially in the health sector. Cultivation of Family Medicinal Plants is a form of maintenance and care for the environment. Based on the Regulation of the Minister of Public Works Number 5 of 2008 concerning Guidelines for Provision and Utilization of Green Open Space in Urban Areas, each city is targeted to have 30 percent of green open space. Of 30 percent, 20 percent is public green open space and 10 percent is private green open space. According to the Head of the Controlling Office for Green Open Spaces, Ashari, in Bekasi, the green open space in Bekasi is only 15 percent and it is difficult to meet the 30 percent figure. In the regulation, there is a calculation of 10 percent of private green open space from urban green open space. So it is necessary to hold outreach activities or the habit of planting and caring for plants or trees in order to help the development of urban green open spaces through the habit of caring for the green environment to the community, especially in RW04 Kel. Sepanjangjaya Kec. Rawalumbu Bekasi City is carried out in the home environment. This activity will be held on March 16, 2022, in RW04 Kel. Sepanjangjaya Kec. Rawalumbu. This cultivation socialization activity will be carried out by methods in the form of counseling and delivery of plants in the form of seeds of Family Medicinal Plants as well as an understanding of how to care for and the benefits of these plants.